2006
DOI: 10.1038/sj.jhh.1002038
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure response to calcium supplementation: a meta-analysis of randomized controlled trials

Abstract: Calcium plays a role in blood pressure (BP) regulation, but the importance of supplemental calcium intake for the prevention of hypertension is still debated. We conducted a meta-analysis of randomized controlled trials to determine the effect of calcium supplementation on BP. A systematic search for randomized trials of calcium supplementation and BP in non-pregnant subjects was performed in Medline from 1966 to June 2003. Seventy-one trials were identified, 40 of which met the criteria for meta-analysis (tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
147
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 240 publications
(162 citation statements)
references
References 49 publications
10
147
1
4
Order By: Relevance
“…It has been proposed that the bloodpressure-lowering effects of calcium supplementation alone tend to be greatest in those with the lowest dietary calcium intakes (o600 mg per day) before supplementation (Reid et al, 2005) and/or those who are hypertensive (Allender et al, 1996). Similarly, several meta-analyses have failed to detect a blood-pressure-lowering effect of calcium supplementation with intakes around 1000-1200 mg per day in groups with a wide range of usual calcium intakes (Dickinson et al, 2006;van Mierlo et al, 2006). Furthermore, because only approximately 30% of the men in our study were classified as hypertensive at baseline, it is possible that the lack of an effect of calcium plus vitamin D 3 supplementation in our study, and in several previous trials (Orwoll and Oviatt, 1990;Pan et al, 1993;Major et al, 2007), was due to the fact that the participants in our study had adequate calcium intakes (B1000 mg per day) and serum 25(OH)D concentrations (B75 nmol/l) and/or were normotensive before supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the bloodpressure-lowering effects of calcium supplementation alone tend to be greatest in those with the lowest dietary calcium intakes (o600 mg per day) before supplementation (Reid et al, 2005) and/or those who are hypertensive (Allender et al, 1996). Similarly, several meta-analyses have failed to detect a blood-pressure-lowering effect of calcium supplementation with intakes around 1000-1200 mg per day in groups with a wide range of usual calcium intakes (Dickinson et al, 2006;van Mierlo et al, 2006). Furthermore, because only approximately 30% of the men in our study were classified as hypertensive at baseline, it is possible that the lack of an effect of calcium plus vitamin D 3 supplementation in our study, and in several previous trials (Orwoll and Oviatt, 1990;Pan et al, 1993;Major et al, 2007), was due to the fact that the participants in our study had adequate calcium intakes (B1000 mg per day) and serum 25(OH)D concentrations (B75 nmol/l) and/or were normotensive before supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…63 Vitamin E is a weak antioxidant that increases the circulating levels of vitamin C. 64 Vitamin E should be limited to 200 IU and should not be taken with aspirin. 16 Substituting green tea for other beverages, together with 1000 mg of vitamin C and 200 mg of vitamin E daily, would be the least expensive choice for achieving good levels of antioxidants.…”
Section: Other Factorsmentioning
confidence: 99%
“…Epidemiological as well as intervention studies have shown an inverse relationship between Ca intake and blood pressure (37,38) . Several potential mechanisms may explain the positive effect of Ca on blood pressure, including reduced membrane permeability to monovalent and divalent cations, reduced intracellular Ca levels, decreased concentrations of Ca-regulating hormones, reduced sympathetic nervous system activity, and altered metabolism of other electrolytes, for example, increased Na excretion (39) .…”
Section: Effects Of Calcium On Blood Pressurementioning
confidence: 99%